Pengaruh Cognitive Dissonance Bias, Overconfidence Bias Dan Herding Bias Terhadap Pengambilan Keputusan Investasi - Dila Afriani; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine whether cognitive dissonance bias, overconfidence bias and herding bias have a significant effect on stock investment decision making partially and simultaneously. the sample in this study were students of the Faculty of Economics, Padang State University. The sampling technique was simple random sampling . A total of 133 questionnaires were returned in complete condition and processed. by using multiple linear regression techniques, the results show that cognitive dissonance bias and overconfidence bias do not affect stock investment decisions. Herding bias has a positive and significant influence on stock investment decision making.